UPPER CARBONIFEROUS (PENNSYLVANIAN) CONODONTS FROM SOUTH GUIZHOU OF CHINA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
This paper describes in detail che conodont sequence of che Upper Carboniferous (Pennsylvanian) and the upper and lower boundaries in this interval at the Nashui section in Luodian, South Guizhou. The following 23 conodont zones, in descending order, can be recognized: Streptognathodus isolatus, S. wabaunsensis, S. tenuialveus, S. firmus, S. nashuiensis, S. simulator, S. guizhouensis, S. gracilis-S. excelsus, S. cancellosus, S. clavatulus, S. nodocarinatus, Idiognathodus podolskensis, Mesogondolella clarki-Idiognathodus robustus, Diplognathodus orphanus-D. ellesmerensis, ldiognathoides ouachitensis, Streptognathodus expansus, Idiognathoides sulcatus parvus, Neognathodus bassleri-Idiognathodus primulus, N. symmetricus-Idiognathodus primulus, N. symmetricus, Idiognathoides corrugatus-I. pacificus, I. sinuatus, I. sulcatus sulcatus and Declinognathodus noduliferus zones. The first occurrences of Streptognathodus isolatus and Declinognathodus noduliferus afe recognized at the bases of che Permian and the Upper Carboniferous (Pennsylvanian), respectively. The Upper Carboniferous (Pennsylvanian) conodont sequences are discussed and based on these conodont sequences, correlations between Upper Carboniferous (Pennsylvanian) Stages in Chinese and Russian sections, as well as North America are discussed. Additionally, eight new conodont species are also described in this paper.